Evidence of exposure to Leptospira spp. in dogs at a zoonosis control center in Brazil - Albuquerque, Mírian da Rocha; Reis, Thalita Amaral dos; Rocha, Katarine de Souza; Brito, Jacqueline da Silva; Mesquita, Gleiciane Schupp de Sena; Silva, Andreia Ferreira da; Honório, Betsy Emely Tavares; Maues, Marcelino Antônio Costa; Abel, Isis; Moraes, Carla Cristina Guimarães de (Revista Acadêmica Ciência Animal, 2020)
Evidence of exposure to Leptospira spp. in dogs housed in the kennel of the Zoonosis Control Center of Belém, Pará, Brazil, was investigated. Whole blood and serum samples from 145 dogs were investigated using the polymerase chain reaction (PCR) and microscopic agglutination test (MAT), respectively. A total of 64.14% of the dogs were found to be seropositive for Leptospira spp., with the most frequent serogroup being Djasiman (39.73%). However, PCR results revealed that all of the dogs were negative for Leptospira spp. DNA. Although the results of the study suggest the animals did not currently have leptospires in blood, they only show circulating anti-Leptospira spp. antibodies, implying prior contact with the bacteria.